2016
DOI: 10.1371/journal.pone.0168490
|View full text |Cite
|
Sign up to set email alerts
|

The Coupling of Peripheral Blood Pressure and Ventilatory Responses during Exercise in Young Adults with Cystic Fibrosis

Abstract: PurposeCystic fibrosis (CF) is commonly recognized as a pulmonary disease associated with reduced airway function. Another primary symptom of CF is low exercise capacity where ventilation and gas-exchange are exacerbated. However, an independent link between pathophysiology of the pulmonary system and abnormal ventilatory and gas-exchange responses during cardiopulmonary exercise testing (CPET) has not been established in CF. Complicating this understanding, accumulating evidence suggests CF demonstrate abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
2
5
1
Order By: Relevance
“…Bongers et al also reported a normal ΔV′E/ΔV′CO 2 slope of 27.1 ± 2.9 in 22 adolescents with CF and an FEV 1 of 79±17%, while the V′E over work rate ratio was elevated. Van Iterson et al examined the ΔV′E/ΔV′CO 2 slope in 16 young adults with CF and an FEV 1 of 73 ± 14%predicted in comparison to healthy controls. In their study, patients with CF had higher ΔV′E/ΔV′CO 2 slopes (38 ± 4) than healthy controls (28 ± 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bongers et al also reported a normal ΔV′E/ΔV′CO 2 slope of 27.1 ± 2.9 in 22 adolescents with CF and an FEV 1 of 79±17%, while the V′E over work rate ratio was elevated. Van Iterson et al examined the ΔV′E/ΔV′CO 2 slope in 16 young adults with CF and an FEV 1 of 73 ± 14%predicted in comparison to healthy controls. In their study, patients with CF had higher ΔV′E/ΔV′CO 2 slopes (38 ± 4) than healthy controls (28 ± 2).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing evidence for the value of the V′E over V′CO 2 ‐relationship in the clinical assessment of people with various diseases, few studies, addressed its role in CF . Van Iterson et al, after testing 16 patients with CF, recently noted that ΔV′E/ΔVC′O 2 slope was increased in contrast to healthy controls but they conclude that “underlying mechanisms remain unclear.”…”
Section: Introductionmentioning
confidence: 99%
“…This is a key omission because contrary to their CPET interpretations and discussion, it is recognized the V̇ E /V̇CO 2 slope and reported thresholds for adults are not translational to adolescent populations and vice‐versa, ventilatory efficiency inversely relates with adult age, and cardiopulmonary disease exacerbates effects of aging on ventilatory inefficiency . The message that ventilatory efficiency is retained in CF based on an interpretation that V̇ E /V̇CO 2 slope does not differ between percent predicted forced expiratory volume in 1‐sec (FEV 1 ) severity, percent predicted V̇O 2peak , and are overall lower than those (of adults) observed elsewhere is not rigorously supported by their data.…”
Section: Human Physiology Is Not the Same Across The Aging Spectrummentioning
confidence: 98%
“…Clinicians and physiologists interested in cardiopulmonary exercise testing (CPET) and ventilatory efficiency appreciate adolescent physiological responses to exercise are not directly translational to the adult, and vice‐versa . It follows that while Kampouras et al provides plentiful discussion involving comparisons between their CPET data and those of our group (Van Iterson et al) reported in adult CF, they missed a critical opportunity to dissect the body of evidence so as to underscore why they consider it is reasonable to compare studies of adults with those of adolescents, particularly in CF. This is a key omission because contrary to their CPET interpretations and discussion, it is recognized the V̇ E /V̇CO 2 slope and reported thresholds for adults are not translational to adolescent populations and vice‐versa, ventilatory efficiency inversely relates with adult age, and cardiopulmonary disease exacerbates effects of aging on ventilatory inefficiency .…”
Section: Human Physiology Is Not the Same Across The Aging Spectrummentioning
confidence: 99%
See 1 more Smart Citation